Reflection-mode time-reversed ultrasonically encoded optical focusing into turbid media - Lai, Puxiang (Society of Photo-Optical Instrumentation Engineers (SPIE), 2011)
Time-reversed ultrasonically encoded (TRUE) optical focusing was recently proposed to deliver light dynamically to a tight region inside a scattering medium. In this letter, we report the first development of a reflection-mode TRUE optical focusing system. A high numerical aperture light guide is used to transmit the diffusely reflected light from a turbid medium to a phase-conjugate mirror (PCM), which is sensitive only to the ultrasound-tagged light. From the PCM, a phase conjugated wavefront of the tagged light is generated and conveyed by the same light guide back to the turbid medium, subsequently converging to the ultrasonic focal zone. We present experimental results from this system, which has the ability to focus light in a highly scattering medium with a round-trip optical penetration thickness (extinction coefficient multiplied by round-trip depth) as large as 160.